Sustainable Intensification Practices Reduce Food Deficit for the Best- and Worst-Off Households in Ethiopia and Mozambique - Wilkus, Erin Lynn; deVoil, Peter; Marenya, Paswel; Snapp, Sieg; Dixon, John; Rodriguez, Daniel (Frontiers in Sustainable Food Systems, 2022)
An adequate food supply is widely recognised as a necessary condition for social development as well as a basic human right. Food deficits are especially common among semi-subsistence farming households in eastern and southern Africa and farm productivity is widely regarded as the locus for enhancing household food outcomes. However, knowledge gaps surrounding benefits of climate smart, productivity-enhancing technologies require attention. This study evaluates benefits of farm management practices associated with sustainable intensification (crop residue retention, minimum tillage, manure application and use of herbicides, pesticides, fertiliser, and improved seeds) for household calorie and protein supplies and demonstrates their scope across households with high-, moderate- and low- likelihoods of calorie and protein deficits. Household-level calorie and protein deficits were estimated from survey data on food production, acquisition and consumption for households in Ethiopia and Mozambique. Multinomial logistic models were used to identify drivers of household food deficit status and logistic model trees established ‘rules of thumb’ to classify households by food deficit status as low, moderate or high likelihood. In Ethiopia, households with a high likelihood of a food deficit experienced especially wet seasons while households with a high likelihood of food deficit in Mozambique experienced especially dry seasons. The practices associated with sustainable intensification and related technologies substantially enhanced food outcomes in groups with a high- and a low-likelihood of food deficit, and benefits were high for the best-off households. Benefits of sustainable intensification technologies were not observed for households with a moderate likelihood of a food deficit and some technologies even increased risk. The sustainable intensification practices assessed here were associated with improved food outcomes yet benefits were limited in scope for households of intermediate status. Thus, there is a need to expand the technical options available to reduce food deficit.